2010
DOI: 10.1109/tmi.2010.2047113
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Bounds and System Design for Multipinhole SPECT

Abstract: Abstract-The pinhole camera in single photon emission computed tomography (SPECT) has an inherent trade-off between resolution and sensitivity. Recent systems overcome this to some extent by utilizing multiple pinholes distributed around the imaging object. The present work is a theoretical study on how to optimally construct such systems. We use an analytic model to analyze the multipinhole SPECT geometry and identify the underlying tradeoffs. One of the results is the derivation of the upper bound for the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…To determine the optimal configuration of our high space-bandwidth scintillation detectors, this study used a theoretical optimization method [23]. The resulting 'optimal' systems were simulated and good sampling was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the optimal configuration of our high space-bandwidth scintillation detectors, this study used a theoretical optimization method [23]. The resulting 'optimal' systems were simulated and good sampling was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…For system optimization, we refer to Nillius and Danielson [23]. Others have published 95 multi-pinhole SPECT optimization procedures for human brain imaging [16].…”
Section: B System Optimizationmentioning
confidence: 99%
“…Table I shows the tested configuration parameters, including the n, D, F, multiplexing degree (MUX), pinhole diameter (d), and open angle of the pinhole (α). The initial spatial resolution (R 0 ) and sensitivity (S 0 ) can be calculated by the geometric analytic model [9]:…”
Section: A Determination Of the Magnification And The Number Of Pinhmentioning
confidence: 99%
“…Subsequently, the AUC of the designed multi-pinhole micro-SPECT can be evaluated with the simulated human observer. Besides, the spatial resolution is estimated by the Fourier crosstalk calculations as described in [9]. Moreover, a hot-rod phantom as shown in Fig.…”
Section: Evaluation Of the System Performancementioning
confidence: 99%
“…In order to determine the optimal MPH collimator design, Nillius et al [2] proposed an analytical model and showed that the image quality in terms of resolution and detection efficiency are related to several parameters: the diameter of FOV (d), radii-of-rotation (I), collimator length (L I), detector intrinsic resolution (R,) and the size of the active detector area (A). Those MPH collimator configuration parameters can be determined for a given system resolution (R,) and FOV (d) in order to optimize the detection efficiency (S).…”
Section: Designmentioning
confidence: 99%